Journal Of Molluscan Studies - Journal Of Molluscan Studies (Oxford University Press, 2026)
The Journal of Molluscan Studies accepts papers on all aspects of the study of molluscs. These include systematics, molecular genetics, palaeontology, ecology, evolution, and physiology. Where the topic is in a specialized field (e.g. parasitology, neurobiology, biochemistry, molecular biology), submissions will still be accepted as long as the mollusc is the principal focus of the study, and not incidental or simply a convenient experimental animal. Papers with a focus on fisheries biology, aquaculture, and control of molluscan pests will be accepted only if they include significant advances in molluscan biology. While systematic papers are encouraged, descriptions of single new taxa will only be considered if they include some ‘added value’, for example in the form of new information on anatomy or distribution, or if they are presented in the context of a systematic revision or phylogenetic analysis of the group.
FI 0.63
Q2
Keywords: Life Sciences; Marine Biology; Acuerdos transformativos; Transformative agreements; Moluscos; Biología de moluscos; Ecología; Evolución; Taxonomía